Resolution of Q Fever–Associated Cryoglobulinemia With Anti-CD20 Monoclonal Antibody Treatment. (January 2017) - Hawkins, Kellie L.; Janoff, Edward N.; Janson, Robert W.
Immunologic phenomena can complicate chronic infections with Coxiella burnetii (Q fever), including immune complex deposition causing vasculitis, neuropathy, and glomerulonephritis. We describe the case of a man with Q fever endocarditis, mixed cryoglobulinemia, and life-threatening vasculitis driven by immune complex deposition who was successfully treated with B cell depleting therapy (rituximab).